Injection-Locked Quantum-Dash Laser in Far L-Band 192 Gbit/s DWDM Transmission - Mohammed Zahed Mustafa Khan; Emad A. Alkhazraji; Amr Mohamed Ragheb; Maged Abdullah Esmail; Qazi Tareq; Habib Ali Fathallah; Khurram Karim Qureshi; Saleh Alshebeili (IEEE Photonics Journal, 2020)
Injection locked quantum-dash laser diode-based comb source is employed in wavelength-division multiplexed (WDM) optical transmission covering ∼1610 nm L-band optical telecommunication window. An aggregate data rate of 192 Gbits/s (3 × 32 GBaud-QPSK reaching 7% FEC overhead) is demonstrated over three 50 GHz separated channels in coherent transmission over a 10 km-long single mode fiber. A thorough investigation of the radio-frequency (RF) characteristics of all channels is carried out in terms of the linewidth, phase, and frequency noises, showing minimum values of 44 kHz, −80 dBc/Hz, and 5.2 × 1011 Hz2/Hz, respectively. Also, an integrated average relative intensity noise of ∼−132 dB/Hz is reported for the central channel. To the best of our knowledge, this constitutes the first report and demonstration of a dense WDM (DWDM) in an extended L-band regime using a comb source.